Whole genome characterization of feline coronaviruses in Thailand: evidence of genetic recombination and mutation M1058L in pathotype switch - Phyu, Eaint Min; Charoenkul, Kamonpan; Nasamran, Chanakarn; Chamsai, Ekkapat; Thaw, Yu Nandi; Phyu, Hnin Wai; Soe, Han Win; Chaiyawong, Supassama; Amonsin, Alongkorn (Frontiers in Veterinary Science, 2025)
Feline coronavirus (FCoV) is a significant pathogen that infects the feline population worldwide. FCoV can cause mild enteric disease and a fatal systemic disease called feline infectious peritonitis (FIP). In this study, a cross-sectional survey of FCoV in domestic cats from small animal hospitals in Thailand was conducted from January to December 2021. Our result showed that out of 238 samples tested for FCoV using 3’ UTR-specific RT-PCR, 18.7% (28/150) of asymptomatic cats and 25.5% (12/47) of cats with unknown status tested positive for FCoVs. Additionally, 51.2% (21/41) of cats with suspected FIP were found to be positive for FCoVs. Genotype identification using S gene-specific RT-PCR showed that all FCoV-positive samples (n = 61) were FCoV type I. This study obtained the whole genome sequences (n = 3) and S gene sequences (n = 21) of Thai-FCoVs. Notably, this study is the first to report the whole genome of Thai-FCoV. Phylogenetic analysis indicated that Thai-FCoVs were closely related to FCoVs from China and Europe. Additionally, the Thai-FCoVs exhibited specific amino acid substitutions (M1058L) associated with the pathotype switch. Recombination events were found to mainly occur in the ORF1ab and S gene regions of Thai-FCoVs. This study provides insights into the occurrence, genetic diversity, virulence amino acid mutations, and potential recombination of FCoVs in the domestic cat population in Thailand, contributing to our understanding of FCoV epidemiology.